2021
DOI: 10.3390/tropicalmed6020097
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Operational Research: Case Studies from the Field of Tuberculosis and Lessons Learnt

Abstract: Real-time operational research can be defined as research on strategies or interventions to assess if they are feasible, working as planned, scalable and effective. The research involves primary data collection, periodic analysis during the conduct of the study and dissemination of the findings to policy makers for timely action. This paper aims to illustrate the use of real-time operational research and discuss how to make it happen. Four case studies are presented from the field of tuberculosis. These includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This PEA study found that evidence synthesis and utilisation skills are vital among governments, research and implementing partners to inform the decision-making process 71 72. Research must be prioritised at the country and regional level with adequate dissemination capacity to inform policy and practice 73–75. Different political prioritisations often impede these, such as poor governance and limited financial and, budgetary prioritisation 64…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This PEA study found that evidence synthesis and utilisation skills are vital among governments, research and implementing partners to inform the decision-making process 71 72. Research must be prioritised at the country and regional level with adequate dissemination capacity to inform policy and practice 73–75. Different political prioritisations often impede these, such as poor governance and limited financial and, budgetary prioritisation 64…”
Section: Discussionmentioning
confidence: 98%
“…71 72 Research must be prioritised at the country and regional level with adequate dissemination capacity to inform policy and practice. [73][74][75] Different political prioritisations often impede these, such as poor governance and limited financial and, budgetary prioritisation. 64 On the other hand, the researchers need to assist TB implementers in identifying the issues contributing to gender disparity in seeking healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to the growing evidence showing that countries and communities need to design contextually appropriate and stakeholder-informed strategies that adapt active case finding for TB during the COVID-19 pandemic for the continuity of TB services [25][26][27][28][29]. In a summary of three operation research studies conducted in the capital cities of three African countries (Kenya, Malawi, and Zimbabwe), Harries et al assessed whether real-time monthly surveillance of TB and HIV activities compared with quarterly surveillance would minimize the anticipated negative impact of COVID-19 pandemic on TB and HIV services [30]. The three studies showed a decline of 31.2%, 40.6%, and 45.6% in the numbers of people presenting with presumptive pulmonary TB for investigation in the three respective countries for the two periods (March 2020-February 2021 compared to the immediate pre-COVID-19 period of March 2019-February 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings add to the growing evidence showing that countries and communities should design contextually appropriate and stakeholder informed interventions that adapt active case nding for TB during the COVID-19 pandemic for continuity of TB services [22][23][24][25][26]. In a summary of three operation researches conducted in the capital cities of three African countries (Kenya, Zimbabwe and Malawi), to assess whether a real-time monthly surveillance of TB and HIV activities instead of the usual quarterly surveillance might help to counteract the anticipated negative impact on TB and HIV services, Harries et al [27] demonstrated that there was a decline of 31.2%, 45.6% and 40.6% in the numbers of people presenting with presumptive pulmonary TB for investigation in the three respective countries from March 2020-February 2021 compared to the immediate pre COVID-19 period of March 2019-February 2020. Following the institution of measures to improve TB case detection, there was only a 5% increase in the numbers of people presenting with presumptive pulmonary TB for investigation in Kenya while the numbers in Zimbabwe and Malawi remained far below the baseline period.…”
Section: Discussionmentioning
confidence: 99%